Vínculos afectivos en la familia post divorcio. - Ortiz Amaya, Angie Geovanna (2015)
In order to highlight the affective bonds in the post-divorce family, was taken as a general goal describe the attachment styles in the family after the divorce from the psychoanalytic approach. To substantiate the theory behind this research is taken as a reference the postulates of Bowlby on his theory of attachment and bonding, this author defines the attachment as the need of every human being to be linked affectively with your figure for attachment, subsequent to this Mary Ainsworth with the types of attachment discovered using the strange situation in infants, and at the end the attachment styles that are proposed for the adults, submitted by Bartholomew. This research was based on a mixed study, narrative cutting, using a descriptive process. We used the biographical, analytical and inductive. To determine the attachment styles in the family divorced is applied to the Argentina of Attachment Styles in conjunction with other techniques such as anamnesis and semistructured interview. The results showed unsafe attachments specifically fearful in the father, anxious in the mother and avoidant in the son. It is recommended that foster communication and affective samples to improve the links in each member, taking these samples affective as a positive point to create in each characteristics that suggest a way to secure attachment.